Emotional hyper‐reactivity and cardiometabolic risk in remitted bipolar patients: a machine learning approach. (15th May 2018) - Dargél, A. A.; Roussel, F.; Volant, S.; Etain, B.; Grant, R.; Azorin, J.‐M.; M'Bailara, K.; Bellivier, F.; Bougerol, T.; Kahn, J.‐P.; Roux, P.; Aubin, V.; et al.
Abstract : Objective: Remitted bipolar disorder (BD) patients frequently present with chronic mood instability and emotional hyper‐reactivity, associated with poor psychosocial functioning and low‐grade inflammation. We investigated emotional hyper‐reactivity as a dimension for characterization of remitted BD patients, and clinical and biological factors for identifying those with and without emotional hyper‐reactivity. Method: A total of 635 adult remitted BD patients, evaluated in the French Network of Bipolar Expert Centers from 2010–2015, were assessed for emotional reactivity using the Multidimensional Assessment of Thymic States. Machine learning algorithms were used on clinical and biological variables to enhance characterization of patients. Results: After adjustment, patients with emotional hyper‐reactivity ( n = 306) had significantly higher levels of systolic and diastolic blood pressure ( P < 1.0 × 10 −8 ), high‐sensitivity C‐reactive protein ( P < 1.0 × 10 −8 ), fasting glucose ( P < 2.23 × 10 −6 ), glycated hemoglobin ( P = 0.0008) and suicide attempts ( P = 1.4 × 10 −8 ). Using models of combined clinical and biological factors for distinguishing BD patients with and without emotional hyper‐reactivity, the strongest predictors were: systolic and diastolic blood pressure, fasting glucose, C‐reactive protein and number of suicide attempts. This predictive model identified patients with emotional hyper‐reactivity with 84.9% accuracy. Conclusion: The assessment of emotional hyper‐reactivity in remitted BD patients is clinically relevant, particularly for identifying those at higher risk of cardiometabolic dysfunction, chronic inflammation, and suicide.